Mochlozetes saltensis sp. nov., asociado a Bromeliaceas de la provincia de Salta (Republica Argentina) (Acaricryptostigmata: mochlozetidae) - Bischoff de Alzuet, Alcira Delia (1987)
Mochlozetes saltensis sp. nov., here described and figured, has been found in samples of three different Bromeliaceae- species (Vriesia tucumanensis. Aechmea distichantha and Tillandsia maxima), from "Finca El Rey" National Park, Salta Province, Argentina.